Gênese e desenvolvimento do Grupo Escolar César Bastos no cenário educacional de Rio Verde/GO (1947-1961) - Silva, Maria Aparecida Alves (2013)
This research aims at investigating the process of genesis and installation of the School Group César Bastos as well as identifying the pedagogical practices experienced in the institution in its first fourteen years of operation. This is the second school group of Rio Verde / GO, opened in 1947 and, to date, is devoid of academic research, which justifies such a study. The time frame of the research is the period from 1947 to 1961, because there is abundant documentation that allowed a glimpse of the process of genesis and constitution of this school unit. Moreover, the period under consideration is a time that, nationally, represented an occasion of heated debate between advocates of public and private education, and locally, expressed the inter - relations between these two modalities of financing education. To do so, this research tried to answer the following questions: in what political-economic and socio-cultural contexts does the Group School César Bastos emerge? What is the role performed by the School Group between 1947 and 1961, a period of great political and ideological debate between public and private education in Brazil? What did this institution represent to the city of Rio Verde? What are the relevant features of its educational practice? What was the educational legislation which supported its operation and drove its pedagogical practice? It is, thus , a qualitative research , of documentary character , based on the consultation and analysis of the following sources : minutes of the City Council , messages of the State governors, Organic Law and Regulation of Primary Education of the State of Goiás , minutes of final exams and school festivities , official documents issued by the School Group , as well as interviews with former students , former teachers and former director of the researched institution. The study is organized in three sections. In the first one, the historical, political, economic, social and cultural conditions involved in the emergence of the School Group were contextualized. The second part encompassed the discussion of the inter-relationships between public and private in the genesis and constitution of the institution. Questions related to the school routine were discussed in the third section. As a result, it was found that the School Group César Bastos had its genesis in the private sector, with philanthropic purposes , and was established in 1947 as the People\'s School of Rio Verde , due to the performance of people from the local community, having as maximum exponent the former Congressman César da Cunha Bastos . However, one year and five months after its installation, the school building was completed, and, with the transfer , the school group became a state public school, named Group School César Bastos. Therefore, the installation of the school unit represented for Rio Verde a greater opportunity to access formal education, by the inhabitants of the city and the countryside.